Стінопис нави церкви св. Онуфрія в Посаді Риботицькій (вступні зауваги) - Гротовський, П.Л. (Студії мистецтвознавчі, 2009)
Frescoes in the post-Basilian church in Posada Rybotycka were discovered between 1966–1967 during the opening conservation (only in the altar) attempted by the Conservation Services of the Sanok Open Air Museum. The research of the style of those paintings was begun by A. Różycka Bryzek, who recognised scenes in the sanctuary. She also put forward hypothesis considering the Balkans style connected with the local workshop and suggesting the possibility of paintings’ date after 1443. It also should be mentioned an attempt made by V. Alexandrovich to connect the medallions showing busts of prophets on triumphal arch with the Byzantine-Ruthenian frescoes founded by Ladislaus Jagiello in Wiślica and Sandomierz.